2018
DOI: 10.1002/erv.2647
|View full text |Cite
|
Sign up to set email alerts
|

Negative urgency and the dual pathway model of bulimic symptoms: A longitudinal analysis

Abstract: Objective This study extends the dual pathway model (DPM) of bulimic symptoms by considering the bidirectional effects amongst symptoms of depression, dietary restraint, and bulimia. We also assessed the influence of negative urgency, a personality construct associated with bulimic symptoms, on the DPM. Method Participants were 244 females (Mage = 23.77 years) from the general community. Variables pertinent to the DPM as well as negative urgency were assessed at baseline, and symptoms of depression, dietary re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…It might be related to the fact that, for these ED sub-types, negative affect could have been an important additional severity indicator not considered in the current study. This observation is in line with Stice's dual pathway model for bulimic symptoms (Puccio, Fuller-Tyszkiewicz, Buck, & Krug, 2019;Stice, Shaw, & Nemeroff, 1998), which specifies dietary restraint, a proxy for DT, and negative affect as key variables. It is also in line with various taxometric studies that have continuously revealed a pure 'dietary', and a mixed 'dietarydepressive', sub-type in BN (Chen & Le Grange, 2007;Grilo, 2004), and BED (Grilo, Masheb, & Wilson, 2001).…”
Section: The Distinctiveness Of the Edi-dt Severity Groupssupporting
confidence: 83%
See 1 more Smart Citation
“…It might be related to the fact that, for these ED sub-types, negative affect could have been an important additional severity indicator not considered in the current study. This observation is in line with Stice's dual pathway model for bulimic symptoms (Puccio, Fuller-Tyszkiewicz, Buck, & Krug, 2019;Stice, Shaw, & Nemeroff, 1998), which specifies dietary restraint, a proxy for DT, and negative affect as key variables. It is also in line with various taxometric studies that have continuously revealed a pure 'dietary', and a mixed 'dietarydepressive', sub-type in BN (Chen & Le Grange, 2007;Grilo, 2004), and BED (Grilo, Masheb, & Wilson, 2001).…”
Section: The Distinctiveness Of the Edi-dt Severity Groupssupporting
confidence: 83%
“…Our findings also agree with the broader impulsivity literature in EDs. These studies have shown that impulsive behaviours are linked to ED symptom severity (Mallorqui-Bague et al, 2020;Todisco et al, 2020;Waxman, 2009;Puccio et al, 2019) and a poorer prognosis (Aguera et al, 2017;Fischer, Peterson, & McCarthy, 2013). Our conclusion is, therefore, that, in the absence of sufficient and robust evidence, caution should be exercised regarding conclusive statements suggestive of the validity of the DSM-5 severity specifiers.…”
Section: The Distinctiveness Of the Dsm-5 Severity Categoriesmentioning
confidence: 77%
“…Other work has implicated a failure to engage the vmPFC with loss-of-control eating in overweight and obese girls in response to distress, suggesting that perturbations in such neural circuits may lead to overeating in order to cope with negative affect 43 . More recent research using stress induction, food cues and ecological momentary assessment found that changes in activation in the vmPFC significantly moderated the relationship of affect to binge eating 44 , thereby lending support to models positing negative urgency as being a risk factor for bulimic symptoms 45 .…”
Section: Discussionmentioning
confidence: 87%
“…Higher depression and body dissatisfaction were significantly associated with more BE, in line with previous studies in adolescents [ 51 53 ]; this association with BE could be partially explained by the severity of BD in the individual, which was found to severely affect and predict depression [ 54 ]. In addition, this association could be the result of a reciprocal relationship between depression and BE with one factor being the cause or result of the other [ 55 , 56 ], while some studies suggested the possibility of them sharing common risk factors [ 57 , 58 ]. For example, feeling worthless could be a shared basis for the development and maintenance of depression, and the root for the perceived sense of shame with regard to body self-evaluation [ 55 ].…”
Section: Discussionmentioning
confidence: 99%